Metal (Loid)s in Farmland Soils and Strategies to Reduce Bioavailability - Fayiga AO; Nwoke OC (Open Journal of Environmental Biology - Peertechz Publications, 2017)
High concentrations of heavy metal (loid)s (HMs) in farmland soils reduces crop yield and contaminates the food chain. Exposure to HMs in the diet results in several adverse health effects such as cancer, reproductive health problems and cardiovascular diseases. Understanding the origin and fractionation of these toxic substances will provide direction for reducing their bioavailability in contaminated farmland soils. HMs are added to farmland soils through activities such as irrigation, organic and inorganic fertilization, pest control, and mining. Weathering of parent material and atmospheric deposition can also increase the levels of HMs in the soil. Fractionation of HM contaminated soils provides information on availability of HMs such as Pb, Cd, As, Cr and Cu to soil biota and plants. Several studies have reported that Pb is mostly associated with Fe and manganese oxides (reducible fraction) while Cd is mostly associated with the most mobile fraction (exchangeable fraction). The application of organic and inorganic soil amendments such as vermiculite, zeolite, composts and crop residue to contaminated farmland soils converts HMs from the plant available fractions to the less mobile fractions. HM resistant microbes can change HMs to a less mobile fraction or less mobile oxidation state. The combination of HM resistant microbes, HM tolerant plants, and soil amendments can be used to reduce mobility of HMs in contaminated farmlands.